Opportunity of Constructing a Cargo Terminal – Case Study Brașov International Airport, Romania - Gabriel BRĂTUCU; Gheorghiţa DINCĂ; Marius Sorin DINCĂ; Alexandra (Palade) ZAMFIRACHE (Transylvanian Review of Administrative Sciences, 2017)
Air transport and especially air cargo transport became ever more important during the last 25 years, with a signifi cant impact upon economic development. Air cargo transport supports regional economic development, provided there is suffi cient local demand for its services. In our study, we have identifi ed signifi cant elements of the impact a cargo terminal at the International Brașov-Ghimbav Airport would have upon local economic development. For this purpose, we have conducted a quantitative market research. We have reached the conclusion that constructing a cargo terminal at the Brașov-Ghimbav Airport is a necessary investment in the current economic context, with an important contribution to the economic development of its surrounding counties. The positive results registered in our study could contribute to improving the economic and fi nancial prospects of Brașov-Ghimbav Airport and attract investors in this project.